2006
DOI: 10.4012/dmj.25.352
|View full text |Cite
|
Sign up to set email alerts
|

Color Change of Newly Developed Esthetic Restorative Material Immersed in Food-simulating Solutions

Abstract: Recently, an esthetic tooth coating material has been developed. The material consisted of a primer solution, a base coat, and a top coat. The purpose of this study, therefore, was to evaluate the color change of this tooth coating material and two resin composites after immersion in food-simulating, staining solutions. To this end, the newly developed coating material with and without its top coat, a flowable resin composite, and a hybrid resin composite were employed for the evaluation.The specimens were sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 18 publications
1
48
0
4
Order By: Relevance
“…Some discoloration is easier to remove than others. 2,3,18,20,28 Although extrinsic factors cause the most discoloration, intrinsic factors involved in the staining process must be considered because they are irreversible and cannot be removed nor bleached, although teeth can be successfully bleached.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some discoloration is easier to remove than others. 2,3,18,20,28 Although extrinsic factors cause the most discoloration, intrinsic factors involved in the staining process must be considered because they are irreversible and cannot be removed nor bleached, although teeth can be successfully bleached.…”
Section: Discussionmentioning
confidence: 99%
“…3,23,24 The results of the present study demonstrated this staining potential, as in other studies. 1,2,3,4,18,24,27,28 Extrinsic discoloration can be removed by daily brushing, a good finishing/polishing technique, and bleaching agents. Some discoloration is easier to remove than others.…”
Section: Discussionmentioning
confidence: 99%
“…A period of four weeks' immersion might be considered by some as too long an experimental period. However; in most in vitro studies 2,3,7,13,26,27,28) , the final period is typically four weeks or more in order to achieve a cumulative staining effect and obtain distinct results. One of the drawbacks in the present investigation might be related with the methodology utilized for the staining procedure.…”
Section: Teethmentioning
confidence: 99%
“…Debido a que no existe una estandarización o protocolo de exposición de las muestras en las bebidas pigmentantes, pues se encuentran en la literatura científica estudios con tiempos de exposición de 1 hora [25] hasta de 4 semanas [29], se decidió exponer los dientes a 10 días consecutivos, equivalentes a la suma de tiempos en que una persona con un alto consumo de bebidas oscuras (Coca-cola ® , vino tinto y café) expone sus dientes a estas sustancias durante un año.…”
Section: Figura 3 Exposición De Los Dientes a Las Tres Bebidas Oscurasunclassified